Evaluation of In Vitro Digested Mulberry Leaf Tea Kombucha: A Functional Fermented Beverage with Antioxidant, Anti-Inflammatory, Antihyperglycemic, and Antihypertensive Potentials - Pitchaporn Wanyo; Tossaporn Chamsai; Nitchara Toontom; Le Ke Nghiep; Kukiat Tudpor (Fermentation)
Oxidative stress and inflammation are critical factors in hypertension and type 2 diabetes mellitus (T2DM). Kombucha, a fermented tea beverage, is enriched with bioactive compounds during fermentation. This study evaluated the antihypertensive, antihyperglycemic, antioxidant, and anti-inflammatory activities of kombucha made from mulberry leaf green tea (MLGT) and black tea (MLBT) during in vitro digestion. The bioaccessibility of 1-deoxynojirimycin (DNJ), γ-aminobutyric acid (GABA), phenolics, and flavonoids was assessed through simulated oral, gastric, and intestinal phases. MLGT kombucha exhibited higher initial antioxidant activity, while MLBT showed greater compound stability and ACE inhibitory activity during digestion. Notably, α-glucosidase inhibition declined significantly in the intestinal phase, in parallel with reduced DNJ and flavonoid content. Strong correlations were observed between specific phenolic acids and bioactivity profiles, highlighting ρ-coumaric and sinapic acids in ACE inhibition and DNJ in antiglycemic activity. These findings demonstrate the functional potential of mulberry leaf kombucha as a beverage to support metabolic health, pending confirmation through in vivo studies.